The development of a smart food container for balanced diet intake - Abdul Malik, Noreha; Gunawan, Teddy Surya; Ibrahim, Siti Noorjannah (Malaysian Medical Association, 2017)
Introduction A balanced diet will ensure the body gets the nutrients needed and help it to build a well immune system that prevents diseases and infections. On the contrary, an unbalanced diet can cause the body susceptible to many diseases such as high blood pressure, diabetes and allergies. Besides, someone will easily become obese if the food intake is not balanced, for example excess carbohydrate intake at every meal. Therefore, this project presents a development of a smart food container for balance diet intake that helps to calculate the total calories for each nutrient contained in the meal. Methods The smart food container consists of a food container with three compartments, three load cells, an Arduino microcontroller, a liquid crystal display (LCD) and a keypad. Each compartment is for different food with different nutrients content namely carbohydrate, protein and vegetables/fruits. A load cell is placed under each compartment to measure the weight of the food in gram. The weight measured is sent to the microcontroller to calculate the total calories. Each nutrient is given a specific coefficient to be multiplied with the weight to calculate the calories. The total calories will be displayed on the LCD together with the recommended calorie intake. The recommended calorie intake is based on the gender, age and the type of meal. The user can reduce or add the food to get the best total calories needed for each of meal time. Results, and Discussion. The total calories and the recommended calorie intake for each nutrient are displayed on the LCD of the smart food container. The total calories calculated can be used as an estimation of calorie intake and is not the real values of calorie intake. This is because when the food is cooked with different recipes, it will have different calories.